Selective accumulation of pharmaceutical residues from 6 different soils by plants: a comparative study on onion, radish, and spinach - Menacherry, Sunil Paul M; Kodešová, Radka; Švecová, Helena; Klement, Aleš; Fér, Miroslav; Nikodem, Antonín; Grabic, Roman (Environmental science and pollution research international, 2023)
The accumulation of six pharmaceuticals of different therapeutic uses has been thoroughly investigated and compared between onion, spinach, and radish plants grown in six soil types. While neutral molecules (e.g., carbamazepine (CAR) and some of its metabolites) were efficiently accumulated and easily translocated to the plant leaves (onion > radish > spinach), the same for ionic (both anionic and cationic) molecules seems to be minor to moderate. The maximum accumulation of CAR crosses 38,000 (onion), 42,000 (radish), and 7000 (spinach) ng g-1 (dry weight) respectively, in which the most majority of them happened within the plant leaves. Among the metabolites, the accumulation of carbamazepine 10,11-epoxide (EPC - a primary CAR metabolite) was approximately 19,000 (onion), 7000 (radish), and 6000 (spinach) ng g-1 (dry weight) respectively. This trend was considerably similar even when all these pharmaceuticals applied together. The accumulation of most other molecules (e.g., citalopram, clindamycin, clindamycin sulfoxide, fexofenadine, irbesartan, and sulfamethoxazole) was restricted to plant roots, except for certain cases (e.g., clindamycin and clindamycin sulfoxide in onion leaves). Our results clearly demonstrated the potential role of this accumulation process on the entrance of pharmaceuticals/metabolites into the food chain, which eventually becomes a threat to associated living biota.
Keywords: Plants; Spinacia oleracea; léčivé přípravky; Onions; česneky; Clindamycin; Pharmaceutical Preparations; Soil Pollutants; látky znečišťující půdu; půda; Translocation of pharmaceuticals in plant; Pharmaceutical accumulation; Raphanus; Metabolism; Soils; klindamycin; Root uptake; Soil; Pharmaceuticals; Plant-dependent transformation of pharmaceuticals; rostliny